St. George's Declaration of Principles for Environmental Sustainability in the OECS (OECS CastriesLC, 2001)
Details the principles of sustainable development by which human conduct affecting the environment is to be guided and judged.
Keywords: SUSTAINABLE DEVELOPMENT